2008
DOI: 10.20996/1819-6446-2008-4-2-53-57
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridine Calcium Antagonists: The Role in Current Therapy of Cardio-Vascular Diseases

Abstract: Государственный научно-исследовательский центр профилактической медицины Росмедтехнологий, Москва Классификация антагонистов кальцияБлокаторы кальциевых каналов, или антагонисты кальция (АК), уже давно широко применяются в кар-диологической практике. С клинической точки зрения, наиболее значимым представляется разделение АК на производные дигидропиридина (селективно блокируют кальциевые каналы в кровеносных сосудах, не обладают негативным дромотропным эффектом, в меньшей сте-пени снижают сократительную способн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thus, these data, that CCB provoke the improvement of IR and glucose tolerance, induced by CT injection, testify about the drawing of Ca 2+ -mechanisms into these processes and about that CCB can further to the correction of hyperglycemia and tissue IR. It is known also, that CCB effect and on other components of metabolic syndrome, revealing athero-protective [70], hypotension [71], lipolytic [72], antianginal, neuro-protective action.…”
Section: Calcium Channel Blockers Improve Insulin Resistancementioning
confidence: 99%
“…Thus, these data, that CCB provoke the improvement of IR and glucose tolerance, induced by CT injection, testify about the drawing of Ca 2+ -mechanisms into these processes and about that CCB can further to the correction of hyperglycemia and tissue IR. It is known also, that CCB effect and on other components of metabolic syndrome, revealing athero-protective [70], hypotension [71], lipolytic [72], antianginal, neuro-protective action.…”
Section: Calcium Channel Blockers Improve Insulin Resistancementioning
confidence: 99%
“…The inhibition by calcium channel blockers (isoptin and nifedipin) hyperglycemic CT effect testifies about the participant of slow potential-depended L-type and chemo-sensitive calcium channels in this effect of hormone [34,35] and gives the basis to consider that calcium channel blockers therapy can be the method of correction of hyperglycemia and insulin-resistance of tissues [36]. Moreover, it is known that calcium channel blockers affect also other components of the metabolic syndrome, revealing athero-protective [37][38][39], hypotensive [40], lipolitic [41,42], anti-anginal, neuroprotective action. It is shown that potential-managed ion channels are effective target of cyto-pharmacological regulation of functional state [43].…”
Section: Calcitonin and Glucose Metabolismmentioning
confidence: 99%